Pengaruh Reward dan Kontrak Psikologis Terhadap Organizational Citizenship Behavior (OCB) Dosen Fkip Universitas Halu Oleo (UHO) - Wa Santi; Mukhneri Mukhtar; Matin - (Peneliti.net, 2018)
The objective of this research is to obtain information about the effect of reward and psychological contract on lecturer organizational citizenship behavior.It was quantitative research with survey methodinof FKIP Halu Oleo University.The research was conducted to all lecturer of FKIP Halu Oleo University (UHO) by using a survey method with path analysis applied in testing hypothesis. The number 156 lecturer as sample was selected by using Slovin formula.The research conclude: (1) Thereis a direct positive effect of reward on Organizational Citizenship Behavior (OCB). (2) There is a direct positive effect of psychological contract on Organizational Citizenship Behavior (OCB). (3) There is a direct positive of reward on psychological contract